SINDROM HORMON ANTIDIURETIK BERLEBIH - Arleen N. Suryatenggara; Dalima A. W. Astrawinata (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Syndrome of Inappropiate Antidiuretic Hormone (SIADH) is a condition caused by excessive antidiuretic hormone (ADH) secretion.High level of ADH increse water reabsorption in the kidney. This syndrome is characterized by hyponatremia, plasma hypo-osmolality,urine osmolality less than 100 mOsm/kg, elevated urine sodium, euvolemia, with normal renal, adrenal, and thyroid function. SIADHcould be the result of ectopic ADH caused by malignant cells, drug-induced, baroreceptor lesion, and other problems. Main treatmentfor SIADH is intended to overcome the underlying diseases. Other approaches are by fluid restriction, salt supplementation, and the useof drugs inducing diabetes insipidus or V2 receptor antagonist.